Expression of BRAF V600E mutant protein in epithelial ovarian tumors - Preusser, Matthias; Capper, David; Berghoff, Anna S.; Horvat, Reinhard; Wrba, Fritz; Schindl, Monika; Schoppmann, Sebastian F.; Deimling, Andreas von; Birner, Peter (Applied immunohistochemistry & molecular morphology, 2013)
Background: Genetic analyses have identified BRAF V600E mutations in a subset of ovarian carcinomas. The aim of this study was to investigate the expression of BRAF V600E aberrant protein using a novel mutation-specific antibody in epithelial ovarian tumors. Methods: We immunohistochemically analyzed expression of V600E-mutant BRAF protein in archival formalin-fixed, paraffin-embedded tissue specimens of 142 epithelial ovarian tumors [98 invasive carcinomas and 44 tumors of low malignant potential (LMP)] using monoclonal antibody VE1. BRAF mutation status was validated in all immunopositive cases and in 6 immunonegative control cases by gene sequencing. Results: We found anti-BRAF V600E immunolabeling in 4 serous carcinomas and 5 serous LMP. Presence of a BRAF V600E mutation was confirmed by sequencing analysis in 6 of the 9 cases (3 LMP tumors, 3 low-grade carcinomas). In 2 partially VE1-positive tumors deriving from 1 patient (1 LMP and 1 contralateral invasive high-grade serous carcinoma), genetic analysis repeatedly resulted in BRAF wild-type, arguing for false-positive immunostaining results. One immunopositive case was repeatedly inconclusive in genetic analysis. In all 6 genetically confirmed cases, BRAF V600E mutant protein expression was homogenous throughout the tumor tissue. Conclusions: We found BRAF V600E mutations in 13% (4/31) of serous LMP and 5% (3/62) of invasive serous carcinomas. No BRAF V600E mutations were detected in nonserous epithelial ovarian tumors. For reliable assessment of the BRAF V600E status in ovarian epithelial tumor samples, an integrated approach using immunohistochemistry and genetic analysis seems advisable, as both methods lead to incorrect results in some cases.